Histopathological changes of chronic cestodes infection in local domesticated ducks (Anas platyrhynchas) in Baghdad city. - Al-Rubaie, Haider Mohammed Ali; Thabit Salih Al-Zubaidi , Mohammed; Sadiq, Nasir (The Iraqi Journal of Veterinary Medicine, 2019)
This study was conducted to investigate the histopathological changes of cestodes chronic intestinal infections in ten local domesticated ducks (Anas platyrhynchas) during the period 1/9/2016- 1/10/2017 in Baghdad city. Results showed severe destruction in the intestinal mucosa ,sloughing and desquamation of the epithelia and severe destruction with distortion or complete loss of the intestinal villi, complete loss of the mucosal and submucosa layers with destruction of intestinal glands and there is a severe infiltration of inflammatory cells mainly mononuclear cells in the lamina propria, and a focal necrosis in the intestinal mucosa.The submucosa showed an infiltration of macrophages and few lymphocytes, severe necrosis , calcification in some mucosal glands or with a cystic dilation with cellular debris in their lumen surrounded by inflammatory cells infiltration mainly mononuclear and plasma cells.The conclusion of the present study was that the cestodes chronic infection cause severe inflammatory response mainly lymphocytes and monocytes in mucosa and sub mucosa and destruction of some intestinal glands of the intestine.